Possible involvement of Wnt11 in colorectal cancer progression. Issue 3 (7th December 2011) - Nishioka, Mitsuaki; Ueno, Koji; Hazama, Shoichi; Okada, Toshiyuki; Sakai, Kouhei; Suehiro, Yutaka; Okayama, Naoko; Hirata, Hiroshi; Oka, Masaaki; Imai, Kohzoh; Dahiya, Rajvir; Hinoda, Yuji
Abstract Our previous report revealed that the expression of Frizzled‐7 (FZD7) in colorectal cancer (CRC) and its possible role in CRC progression. In this study we measured the expression levels of candidate FZD7 ligands, Wnt3 and Wnt11 in colon cancer cell lines (n = 7) and primary CRC tissues (n = 133) by quantitative RT‐PCR. We also examined the functional effects of Wnt11 with the use of Wnt11 transfectants of colon cancer HCT‐116 cells. Wnt11 transfectants showed the increased proliferation and migration/invasion activities compared to mock cells. Western blot analysis of transfectants revealed that phosphorylation of JNK and c‐jun was increased after Wnt11 transfection. Wnt11 mRNA expression was significantly higher in the stage I, II, III, or IV tumor tissues than in non‐tumor tissues (overall P < 0.003), while there was no significant difference in Wnt3 mRNA expression between tumor and non‐tumor tissues. In addition, Wnt11 mRNA expression was significantly higher in patients with recurrence or death after surgery than in those with no recurrence (disease free) after surgery (P = 0.018). We also compared the expression levels of Wnt11 mRNA with those of FZD7 mRNA in the same CRC samples. Wnt11 mRNA expression was significantly higher in patients with higher FZD7 mRNA levels than in those with lower FZD7 mRNA levels (P = 0.0005). The expression levels of Wnt11 mRNA were correlated with those of FZD7 mRNA (P < 0.0001). These data suggest that Wnt11 may play an important role in CRC progression. © 2011 Wiley Periodicals, Inc.